حكم تحديد سن الزواج بين الفقه الإسلامي والقانون الوضعي - سعيد، عبدالستار كريم Said, Abdulsattar Karim (جامعة جيهان أربيل, 2019)
لقد اهتم الإسلام بالزواج اهتماما بالغا، لأنه أخطر وأهم عقد في المجتمع البشري فهو عقد لا تستقيم الحياة بدونه. وقد حرص الإسلام عليه كل الحرص لتقوية هذا البناء وإبعاده عن المشكلات التي قد تؤدي به إلى الانهيار والانحراف، وذلك لتحقيق المقاصد الشرعية من الزواج من سكن نفسي ومودة ورحمة وحماية للفرد والمجتمع من أي انحراف خلقي في غياب الزواج الشرعي مصداقا لقوله تعالى: (وَمِنْ آَيَاتِهِ أَنْ خَلَقَ لَكُمْ مِنْ أَنْفُسِكُمْ أَزْوَاجًا لِتَسْكُنُوا إِلَيْهَا وَجَعَلَ بَيْنَكُمْ مَوَدَّةً وَرَحْمَةً إِنَّ فِي ذَلِكَ لَآَيَاتٍ لِقَوْمٍ يَتَفَكَّرُونَ). وجدير بالذكر فقد ظهرت مؤخرا في العديد من الدول العربية والإسلامية. ومن بينها العراق مسألة تزويج الصغيرات. فأثيرت ضجة كبيرة حول تلك القضية، مما أدى ببعض الدول إلى اللجوء لوضع تشريع جديد لتحديد سن الزواج بسن معينة. وقد تباينت الآراء والأحكام حول قضية زواج الصغيرات. ولا يزال الجدل يحتدم حول هذا الموضوع بين مؤيدين ومعارضين من تخصصات فقهية وقانونية واجتماعية وتربوية فهي من المسائل الحساسة والمهمة في المجتمع لارتباطها الشديد بالواقع، وما تترتب عليه من آثار اجتماعية ونفسية واقتصادية وغيرها. فبينما يرى البعض بأن الرؤية أو التصور الشرعي لهذه القضية لا يمكن إهمالها، وإن النصوص الشرعية هي المهيمنة على مثل هذه القضية، والتي تجيز تزويج الفتاة الصغيرة، وتعتبر أن تحديد سن زواج الفتاة يعد انتهاكا للمعتقدات السائدة في الشريعة الإسلامية. وفي المقابل برى فقهاء آخرون بأن هذه القضية تسيء للفتاة وأسرتها ومجتمعها. بسبب الآثار السلبية التي تعاني منها الزوجة الصغيرة. لكونها غير مهيئة نفسيا وجسديا وفسيولوجيا. ويحتاج أطفالها إلى الرعاية. فضلا عن ذلك فإنها وبحكم صغر سنها لا تدرك معنى الزواج والتزاماته، وحقوق الزوجية والمسؤوليات المترتبة على الزواج مما يؤدي إلى خلل كبير لا يقره الإسلام. وهناك توجها ثالثا يرى بأن زواج الصغيرات على الرغم من إباحته لابد أن يخضع لبعض القيود التي تضيق من الإفادة من مشروعية زواج الصغيرات استنادا على قاعدة شرعية مؤداها (حق ولي الأمر في تقييد المباح). والتي عملت بها غالبية التشريعات العربية والإسلامية. Islam has been considerably concerned with marriage, because it is the most serious and important contract known by human society. Therefore, Islam has been very careful in strengthening its structure and keeping it from the problems leading to collapse and deviation. In order to realize such jurisprudent intents of marriage as psychological quietness, compassion and mercifulness, as well as protecting both the individual and society from any moral deviation. In the absence of the legitimate and valid marriage according to the saying of God the almighty in the holy Quran," And of his signs is that he created for you mates from among yourselves so that you may find tranquility in them. And he planted love and compassion between you. In this are signs of people who reflect". It is worth-bearing in mind that the marriage of young girls has recently appeared in many Islamic and Arab countries, including Iraq. And a dilemma has been excited concerning this topic, which led some states to enact a legislation to limit or restrict the age of marriage. And both the opinions and judgments have variated concerning this subject. And the argument and controversy is still in progress, between opponents and proponents. In juristic, legal, social and educational fields of specializations, for this one of the most sensitive topics in any society, for its close connection with reality, with its social, psychological economic and other effects. Whereas other scientists think that juristic point of view cannot be neglected, and juristic texts are ruling in this topic, which permits the marriage of young girls, and considers that the restriction of the age of marriage is a violation to the beliefs of Islamic jurisprudence. This is from one part, and from the other part some other jurists think that this topic hurts the young girls and her family and society. Because of its bad effects on the young wife. Because she is not prepared psychologically, physically and physiologically. As a result of her young children who need care and attention, furthermore, she does not understand the meaning of the marriage and its obligations and burdens. As well as not understanding the matrimonial rights and responsibilities of the marriage itself. And this topic will often lead to a farreaching disorder in the family life unsupported by Islam. It should also be noted that the marriage of young girls, notwithstanding its being permitted. It should be limited by some restrictions of the benefits of the legitimacy and validity of marriage of young girls, according to a juristic rule concerning the right of the ruler to restrict permitted things. Which has been adopted by most Arab and Islamic legislations.
Keywords: الفقه الإسلامي -- القوانين الوضعية -- الزواج الشرعي -- سن الزواج -- الشريعة الإسلامية